Invisible Sisters : A Memoir - Handler, Jessica (Book collections on Project MUSE., 2015)
When Jessica Handler was eight years old, her younger sister Susie was diagnosed with leukemia. To any family, the diagnosis would have been upending, but to the Handlers, whose youngest daughter, Sarah, had been born with a rare, fatal blood disorder, it was an unimaginable verdict. Struck by the unlikelihood of siblings sick with diametrically opposed illnesses, the medical community labeled the Handlers' situation a bizarre coincidence. To their mother, the girls' unlikely diagnoses constituted a reverse miracle-the sort no one wishes for. By the time she was nine years old, Jessica had beg.